Morālā kaitējuma institūta civiltiesībās iztulkošana - Miķelsone, Gundega (Latvijas Universitāte, 2009)
Pētījums ir veltīts morālā kaitējuma institūta izpratnei Latvijas civiltiesībās. Tā kā CL 1635.pants uzskatāms par morālā kaitējuma institūta civiltiesībās pamatu, bakalaura darbā veikta šā panta (izņemot otrās daļas otro teikumu) interpretācija jeb iztulkošana, izmantojot gramatisko, sistēmisko, vēsturisko un teleoloģisko metodi. Pētījuma pirmajā daļā apskatīta morālā kaitējuma institūta attīstības gaita un piemērošanas problēmas Latvijā, salīdzinot tās ar situāciju Rietumvalstīs, kā arī bijušajā Padomju Savienībā. Otrajā daļā veikta CL 1635.panta gramatiskā iztulkošana. Trešajā daļā CL 1635.pants interpretēts sistēmiski, bet ceturtajā daļā – vēsturiski un teleoloģiski. Veikusi CL 1635.panta gramatisko, sistēmisko, vēsturisko un teleoloģisko interpretāciju, autore atzīst, ka tā taisnīgai piemērošanai nepieciešams izmantot tiesību tālākveidošanu contra legem. Ar šīs juridiskās metodes palīdzību tālākveidotais CL 1635.pants konkretizē, nevis ierobežo Satversmes 92.panta trešajā teikumā un citos pantos garantētās tiesības. Diemžēl nav iespējams prognozēt, vai šādu diezgan sarežģītu tiesību piemērošanu atzīs Latvijas tiesas, tādēļ darba nobeigumā autore piedāvā labāku CL 1635.panta regulējumu.

The investigation is dedicated to understanding of the concept of moral injury within the civil law of Latvia in relation to the respective concept of the right to compensation for moral injury. In order to come to certain conclusions Article No 1635 (except the second sentence of Paragraph 2) of the Civil Law of the Republic of Latvia has been interpreted thoroughly. In the first part of the research the author deals with the course of development and application problems of the concept of moral injury in Latvia, making comparison with their status in western countries as well as in the former Soviet Union. In the second part the grammatical interpretation of Article No 1635 has been realized. In the third part Article No 1635 has been interpreted systemically, but in the fourth part – historically and teleologically. Having interpreted No 1635 of the Civil Law of the Republic of Latvia by making use of grammatical, systemic, historical and teleological methods, the author acknowledges that in order to ensure the equitable application of this norm, it is necessary to use the method of further law-making «contra legem». If Article No 1635 has been developed by the help of the method «contra legem», the norm specifies but not restricts the respective human rights granted by the third sentence of Article No 92 of the Constitution of the Republic of Latvia as well as by other normative acts in force. Unfortunately it is impossible to envisage whether the courts of Latvia would approve of this rather complicated application of rights, therefore within the conclusion of the research work, the author proposes her idea of a better regulation and wording of the norm.
Interpretation of Concept of Moral Injury in Civil Law
Keywords: Juridiskā zinātne